Changes of Peripheral Nerve Function and Vitamin B12 Level in People With Parkinson's Disease - Qiu, Feng; Wu, Yue; Cao, Hui; Liu, Ben; Du, Mingyang; Jiang, Haibo; Li, Shun (Frontiers in Neurology, 2020)
Background and Purpose: Peripheral nerve function plays an important role in balance control. Impairment of peripheral sensory information appears in people with Parkinson's disease (PD). Furthermore, there is a link between peripheral nerve disorders and vitamin B12 level. Here, we studied whether there were deficits of peripheral nerve function and vitamin B12 level, which may lead to decreased postural stability in PD. Methods: Fifty PD and 50 age-matched healthy subjects were enrolled in the study. This study evaluated folic acid and vitamin B12 levels in serum. Postural balance was studied according to the clinical Tinetti scale. Some comprehensive physiological assessments of peripheral nerve functions, including peripheral sensation, the perception of temperature, pain, and touch sensations, were also undertaken in this study. Results: Compared with the control group, vitamin B12 and folic acid were decreased in PD (P < 0.05). Furthermore, the PD group exhibited declines in peripheral nerve functions, including touch, temperature, pain, and nerve conduction velocity (P < 0.05). Statistical tests identified a significant association between decreased peripheral nerve function and poor balance according to the Tinetti scale (P < 0.05). Low vitamin B12 levels were also associated with deficits of peripheral nerve function, cumulative levodopa dose, and poor balance in PD (P < 0.05). Conclusions: Data suggested that peripheral nerve function was impaired in people with PD. Deficits of sensory input and low vitamin B12 level may contribute to balance deficits in PD.